Pengaruh Harga, Kualitas Produk, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Skincare Lucienne Secara Online - Nanda Noviantari Putri; Taharuddin (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: This study uses a quantitative research method with multiple linear regression analysis methods. Data collection through questionnaires using Google Form. The population in this study were all consumers who purchased Lucienne skincare products online with a sample size of 96 respondents using a purposive sampling technique. The results of this study indicate that price and service quality have a negative and insignificant effect on purchasing decisions, while product quality has a positive and significant effect on online purchasing decisions of Lucienne skincare products. Simultaneously, both price, product quality and service quality have a significant effect on purchasing decisions